1972
DOI: 10.1002/eji.1830020118
|View full text |Cite
|
Sign up to set email alerts
|

Protease activity as a possible mechanism of migration inhibitory factor

Abstract: The activity of migration inhibitory factor (MIF), present in the supernatants of specifically and nonspecifically stimulated human lymphocyte cultures, can be blocked by antiproteases of animal and plant origin and by diisopropyl fluorophosphate. MIF, partially purified by column chromatography and zone electrophoresis on polyvinylchloride is blocked in the same way. On the other hand, migration inhibition can be effected by some proteases, especially by cobra venom. These findings are discussed in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The molecular weight of this lymphokine was 23,000 daltons, as determined by gel filtration. Haveman et al (1972) reported an hMIF in supernatants of human lymphocytes sensitized to PPD with a molecular weight range of 30,000 to 60,000 daltons. Three different molecular species of hMIF were found in the supernatants of Con A-stimulated, human, 3.4 ± 1.2 b 31.2 ± 6.1 a 1.8 ± .6 b 1.7 ± .8 b 28.1 ± 3.9 s 3.5 ± 2.6 b 1.2 ± 31.2 ± 2.8 4.9 23.9 1.4 6.8 a 1.6 b 3.6 b 3.0 s .9 b a,b Means within a column with no common superscripts are significantly different (P<.05).…”
Section: Table 6 Percentage Of Migration Inhibition (± Sem) Of Thymumentioning
confidence: 98%
“…The molecular weight of this lymphokine was 23,000 daltons, as determined by gel filtration. Haveman et al (1972) reported an hMIF in supernatants of human lymphocytes sensitized to PPD with a molecular weight range of 30,000 to 60,000 daltons. Three different molecular species of hMIF were found in the supernatants of Con A-stimulated, human, 3.4 ± 1.2 b 31.2 ± 6.1 a 1.8 ± .6 b 1.7 ± .8 b 28.1 ± 3.9 s 3.5 ± 2.6 b 1.2 ± 31.2 ± 2.8 4.9 23.9 1.4 6.8 a 1.6 b 3.6 b 3.0 s .9 b a,b Means within a column with no common superscripts are significantly different (P<.05).…”
Section: Table 6 Percentage Of Migration Inhibition (± Sem) Of Thymumentioning
confidence: 98%
“…Once the macrophage has destroyed the antigen, presumably lymphocyte transformation would cease and MIF/MAF activity would cease. Since phagocytizing macrophages are known to release significant quantities of different proteases into the extracellular medium [29], the MIF or MAF activity would be continuously eliminated by proteolysis [30]. Thus, the cycle of lymphocyte transformation leading to macrophage phagocytosis could be interrupted.…”
Section: Macrophage Migration Inhibitory Factor (Mif) and Macrophage mentioning
confidence: 99%
“…Using this assay procedure and partially purified thymus-derived M I F activity, we have explored the effects of derivatives of epsilon-amino-caproic acid (EACA) upon M I F activity in vitro proceeding from the observation of Havemann et al (3) that inhibitors of proteolytic activity such as soybean and lima bean trypsin inhibitors were capable of inhibiting the MIF activity obtained from the supernatant of transformed lymphocytes. The results of these studies, as reported below, indicate that derivatives of the protease inhibitor EACA are also capable of significantly inhibiting M I F at concentrations of the order of M and that the ideal compound (active at M ) has four methyl groups between an acetylated amino group and a free carboxyl group.…”
mentioning
confidence: 99%